2019
DOI: 10.1111/opn.12258
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of older persons in nursing homes after the implementation of a knowledge‐based palliative care intervention

Abstract: BackgroundThe goals of palliative care are to relieve suffering and promote quality of life. Palliative care for older persons has been less prioritised than palliative care for younger people with cancer, which may lead to unnecessary suffering and decreased quality of life at the final stage of life.AimTo evaluate whether a palliative care intervention had any influence on the perceived quality of life of older persons (≥65 years).MethodsThis study was conducted as a complex intervention performed with an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
0
13
0
1
Order By: Relevance
“…Resident outcomes were assessed in terms of quality of care, quality of life, quality of death, care satisfaction, symptom experience, comfort and staff and resident/family communication, which had been mostly assessed or reported by family/carers or staff members. One study directly asked residents regarding their quality of life (Bökberg, Behm, & Ahlström, 2019), while five studies conducted surveys to deceased residents’ family. Resident outcome measures that were selected to assess quality of life, comfort, care quality, symptom management and satisfaction included Symptom Management for EOL Care in Dementia, the Comfort Assessment in Dying scales (Van den Block et al, 2019; Verreault et al, 2018) and the Quality of Dying in Long‐Term Care (Hall, Longhurst, & Higginson, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Resident outcomes were assessed in terms of quality of care, quality of life, quality of death, care satisfaction, symptom experience, comfort and staff and resident/family communication, which had been mostly assessed or reported by family/carers or staff members. One study directly asked residents regarding their quality of life (Bökberg, Behm, & Ahlström, 2019), while five studies conducted surveys to deceased residents’ family. Resident outcome measures that were selected to assess quality of life, comfort, care quality, symptom management and satisfaction included Symptom Management for EOL Care in Dementia, the Comfort Assessment in Dying scales (Van den Block et al, 2019; Verreault et al, 2018) and the Quality of Dying in Long‐Term Care (Hall, Longhurst, & Higginson, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…71 Training on violence prevention and detection 1 Teresi et al 72 Staff training targeting resident-to-resident elder mistreatment. 72 Training on palliative care assessment 2 Bökberg et al 73 Hanson et al 74 Training on palliative care need identification and symptom management for staff in nursing home, 73 Goals of care to improve decision making and palliative care for PWAD. 74 Training to manage pain 1 Rostad et al 75 Training on pain assessment and analgesic use on residents with severe dementia.…”
Section: Interventions For the Maintenance Of Intrinsic Capacitymentioning
confidence: 99%
“…The evaluation of the KUPA project addresses several different outcomes reported in previous papers (Alftberg et al, ; Bökberg Behm, & Ahlström, , ; Bökberg, Behm, Wallerstedt, & Ahlström, ; Bökberg et al, ) and will be further reported in future papers. The intervention was implemented during a 6‐month period with different staff and front leaders (8–12 in each nursing home) in 20 nursing homes in two different counties in southern Sweden (Ahlström et al, ).…”
Section: Methodsmentioning
confidence: 71%